Effect of Heat Treatment and Anodizing of Aluminum 2024 on Hardness Test and Impact Test - Sholechuddin Rhomadloni, Putra; Junipitoyo, Bambang; Suprapto, Yuyun (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Aluminum alloy 2024 is an alloy that is widely used in the aircraft industry, especially in the structure. This research was carried out with the Vikers hardness test method and the Charpy Impact test to determine the mechanical properties of the 2024 Aluminum alloy after going through the Solution heat treatment process with a temperature of 505oC with variations in natural aging time for 5, 7, 9, 11 days and through the Anodizing process with a time of 30 minutes and carried out Vikers hardness testing and Charpy Impact testing. The final results obtained in the Vickers hardness test obtained the highest average value in specimens that went through solution heat treatment with variations in natural aging time for 11 days and through the anodizing process of 80.2 HVN. Heat treatment and anodizing can improve mechanical properties in terms of toughness and hardness of the material, namely by using a stable temperature during heat treatment. In the Impact test, the highest average toughness value is obtained in specimens that go through solution heat treatment with a variation of natural aging time for 11 days and through the anodizing process of 0.76 J/mm². This shows that the Heat Treatment and Anodizing process affects the hardness and impact value of 2024 aluminum.